Experimental and numerical investigation of thermoplastic honeycomb sandwich structures under bending loading. (October 2020) - Gao, Xu; Zhang, Miaomiao; Huang, Yaodong; Sang, Lin; Hou, Wenbin
Abstract: Sandwich structures have attracted increasing attention in engineering applications due to their lightweight effect and energy absorbing capacity. In the current work, fully-thermoplastic honeycomb sandwich structures with 100% recyclability were developed, which consisted of continuous glass fiber-reinforced polypropylene (PP/GF) face sheets, polypropylene (PP) core and assembled using thermoplastic adhesive films. The experimental tests and numerical analysis were conducted to investigate the bending behavior and energy absorption of PP-based sandwich structures. Firstly, a series of three-point bending experiments were tested and the influences of structural factors on bending behaviors were investigated. The typical deformation modes were explored and the damaged microstructure of face-sheets were observed. Finite element models of the sandwich structures were developed to capture the deformation process, and the simulation results were validated with the experimental data. Afterwards, a multi-objective optimization was performed to seek for the maximum specific energy absorption together with the minimum initial peak force simultaneously. Response surface method was adopted to construct objective response functions and used for the defined optimization problem. Highlights: Propose a novel fully-thermoplastic honeycomb sandwich beams. Large deformation and recovery ability of PP-based sandwich beams under three-point bending. Establish RSM to formulate the mathematical relationship between bending response and peak force in four levels.